Understanding Purchase Intentions on DOTA 2 Virtual Items: A Study of Indonesian Players' Game Satisfaction and Emotional Value - Suryawan, Tjokorda Gde Agung Wijaya Kesuma; Sumerta, I Komang; Vijaya, Made Pramana (Jurnal Ekonomi, 2024)
In an ever-changing digital game climate, where players' needs are always changing, the Dota 2 developers find themselves at the forefront of the task of providing new virtual items. This study delves into the challenging domain of virtual creation, focusing on the captivating features of the Battle Pass, formerly known as the Compendium. The primary purpose of this research is to undertake an in-depth study of the effects of game satisfaction and emotional value on the purchase intention of Dota 2 Indonesia Facebook group members, particularly those who have been involved in numerous Battle Pass sales. Purposive random sampling method was used to acquire a total of 96 respondents. Following the distribution of the questionnaire, all data was deemed valid and reliable for analysis utilizing multiple linear regression analysis, determination coefficient analysis, and hypothetical tests (t-test and f-test). Preliminary results show positive and significant effects of game satisfaction and emotional value on purchase intentions for Battle Pass components. Clearly, satisfaction with the game experience appears to be an important determinant in the foundation of purchase intentions, while the positive effect of emotional value on the decision-making process is evident. The practical implications of these findings reach the Dota 2 developers, calling for a strategic focus on improving not only the offensiveness of Battle Pass weapons, but also the entire game experience. Recommendations include efforts focused on improving the game system, implementing stronger security measures, and improving Dota 2's visual appeal. Additionally, it is recommended to create and manage social media accounts to expand user reach and community involvement. This research advances the understanding of the virtual economy, providing valuable insight into the complex processes that shape user behavior in online games. Subsequently, this research undoubtedly contributes to the marketing field by shedding light on the intricacies of gamer satisfaction and emotional value in the context of virtual item purchases. The implications of these findings underscore the importance for game developers to prioritize user satisfaction, security, and aesthetics to foster a positive virtual economy and sustain user engagement